Métodos de suplementação da enzima fitase em dietas para tilápia do Nilo - Carradore, Rosane (2014)
This study aimed to evaluate different methods of supplementation of phytase in diets for Nile tilapia. Three diets since the third were formulated, the first missing phytase (control), the second contained supplementation prior to processing of the diet which was added phytase from the ingredients mixed, added 20% water and extruded at a temperature of 52°C anda third diet with the enzyme for coverage, which we used the spray to enter it after processing, and the treatments that received the enzyme phytase had 1.500 UFA/kg of feed. Regarding the statistical analysis a latin square randomized design was conducted using 204 Nile tilapia, with approximately 30g. At the end of the study protein digestibility, gross energy, ether extract and ash was evaluated, they showed no significant difference, but the calcium digestibility showed a significant difference between treatments with and without phytase on phosphorus digestibility was this difference with the addition of the enzyme. At the end of the experiment, blood sampling 30 fish, where they performed the analysis of phosphorus in the blood, which did not differ significantly in the treatments was performed. Analysis of both phosphate and orthophosphate did not differ significantly among treatments, then was held was held